Auditory neuromarketing in consumer behavior at points of sale in a shopping center in the metropolitan district of Quito - Aguirre Parra, Marcela K; Vasco Vasco, Jorge; Veloz Navarrete, Carlos; Arregui Álvarez, Alexandra (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020DO - 10.36779/mktdescubre.v1iEspecial.571, 2021)
Neuromarketing is currently considered a revolutionary tool, which arises as a product of evolution by combining marketing with neuroscience; Through the analysis of mental and brain processes, through the use of equipment and current marketing trends, with stimuli that create a perception in the senses, it is possible to influence the behavior related to the purchase decisions of consumers and maintain thus their loyalty in front of a brand or commercial store. In this study it was possible to appreciate the auditory perception in stores of a shopping center in the city of Quito; When using biometric neuromarketing equipment, it was possible to observe the brain responses of people to stimuli that were related to hearing obtained from some points of sale in shopping centers. This entire process allows us to know the way in which neuromarketing is currently applied in stores or brands of a shopping center, and thus validate that its correct use generates emotions and feelings in a positive way, in order to determine direct consumer-company associations.